Analysis of service extensible capability for extensible network service model - Zuqin JI; Jun SHEN; Delin DING; Xiaowei CUI (Tongxin xuebao)
The capability of providing network service extensibility is the major demand of next generation network,it is also the main challenge of network service model technology.The extensible network service model was proposed in response to the demand of network development.Firstly,an overview of the basic principles of the extensible network service model was expounded.And then,from the point of view of principle analysis,the service extension capability of the service model was qualitatively analyzed.Finally,using the analytic method of network service extensible capability,the service extension capability of the service model was quantitative analyzed from two perspectives of theory and practical application.The qualitative analysis and the quantitative analysis show that the extensible network service model has strong service extensible capability.